Formulasi Bagea Berbahan Ekstrak Tepung Singkong dan Gonad Diadema Setosum (Sea urchins) sebagai Makanan Alternatif pada Ibu Hamil - Banudi, La; Anasiru, M. Anas; Petrus, Petrus; Leksono, Purnomo (Poltekkes Kemenkes Kendari, 2017)
The hope of this research is to establish manateau kanji extract as a formula for bagea production that comes with gonad diadem setosum (sea urchins), which is rich in nutrients and therefore ideal for women pregnant. Cassava kanji extract can be used as a food formula ingredient to make a range of food formula The goal of this study is to examine the formula of bagea made from cassava flour extract and Gonad Diadema Setosum (Sea urchins) as an aging food in pregnant women. Pre-experiment design in the manufacture of bagea solution. The highest favorite amount for cassava flour bagea is BTP 2 (sago flour 50, cassava flour 50) with a value of 3.26. In addition, the highest level of favorite in the manufacture of bagea made from cassava flour and the addition of gonad is BTP 2 (sago flour 50, cassava flour 50 and gonad 20) In order to increase the preferred value of bagea with the addition of cassava flour and gonad, it is important to add certain ingredients to add flavor to remove odor.